A Novel Multi-Exon Deletion of PACS1 in a Three-Generation Pedigree: Supplements to PACS1 Neurodevelopmental Disorder Spectrum - Liu, Yuan; Ding, Hongke; Yan, Tizhen; Liu, Ling; Yu, Lihua; Huang, Yanlin; Li, Fake; Zeng, Yukun; Huang, Weiwei; Zhang, Yan; Yin, Aihua (Frontiers in Genetics, 2021)
PACS1 Neurodevelopmental Disorder (PACS1-NDD) is a category of rare disorder characterized by intellectual disability, speech delay, dysmorphic facial features, and developmental delay. Other various physical abnormalities of PACS1-NDD might involve all organs and systems. Notably, there were only 2 unique missense mutations (c.607C>T (p.Arg203Trp) & c.608G>A (p.Arg203Gln)) in PACS1 that had been identified as pathogenic variants for PACS1-NDD or Schuurs-Hoeijmakers syndrome (SHMS). Previous reports suggested that these common missense variants were likely to act through dominant-negative or gain-of-function effects manner. It’s still uncertain that whether the intragenic deletion or duplication in PACS1 will be disease-causing. By using whole exome sequencing, we first identified a novel heterozygous multi-exon deletion covering exons 12-24 in PACS1 (NM_018026) in four individuals (two brothers, their father and grandfather) in a three-generation family. The younger brother was referred to our center prenatally and was evaluated before and after the birth. Unlike the SHMS, no typical dysmorphic facial features, intellectual problems, structural brain anomalies were observed among these four individuals. The brothers showed a mild hypermyotonia of their extremities at the age of 3 months old and recovered over time. Mild speech and cognitive delay were also noticed in the two brothers at their age of 13 and 27 months old, respectively. However, their father and grandfather showed normal language and cognitive competence. This study might supplement the spectrum of PACS1-NDD and demonstrates that loss of function variation in PACS1 displays no contributions to the typical SHMS which caused by the recurrent c.607C>T (p.Arg203Trp) variant.